Computer Engineering Computer Technology in All Areas of Industry - Mamatova Maxzuna Baxriddinovna (Research Parks Publishers, 2022)
The article deals with computer engineering, logical design, information technology in engineering, the communication capabilities of computers and computer networks, as well as the complexity of the product of industrial production and computer technology in all areas of industry.